2003
DOI: 10.1101/lm.67603
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-Decarboxylase Knockout Mice Show Deficient Nonreinforced Episodic Object Memory, Improved Negatively Reinforced Water-Maze Performance, and Increased Neo- and Ventro-Striatal Dopamine Turnover

Abstract: The brain's histaminergic system has been implicated in hippocampal synaptic plasticity, learning, and memory, as well as brain reward and reinforcement. Our past pharmacological and lesion studies indicated that the brain's histamine system exerts inhibitory effects on the brain's reinforcement respective reward system reciprocal to mesolimbic dopamine systems, thereby modulating learning and memory performance. Given the close functional relationship between brain reinforcement and memory processes, the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 61 publications
(74 reference statements)
0
66
0
Order By: Relevance
“…Previous research showed that HDC-KO mice exhibit lower spontaneous locomotor activity during the dark period (Kubota et al, 2002;Iwabuchi et al, 2004) and reduced exploratory activity in an open field, but normal habituation to a novel environment (Dere et al, 2004). Their behavior is more anxious than controls in the height-fear task and the graded anxiety test (Dere et al, 2003;Acevedo et al, 2006b). Most important, HDC-KO mice show improved water-maze performance during both hidden and cued platform tasks, but exhibit deficient object discrimination based on temporal relationships (Dere et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Previous research showed that HDC-KO mice exhibit lower spontaneous locomotor activity during the dark period (Kubota et al, 2002;Iwabuchi et al, 2004) and reduced exploratory activity in an open field, but normal habituation to a novel environment (Dere et al, 2004). Their behavior is more anxious than controls in the height-fear task and the graded anxiety test (Dere et al, 2003;Acevedo et al, 2006b). Most important, HDC-KO mice show improved water-maze performance during both hidden and cued platform tasks, but exhibit deficient object discrimination based on temporal relationships (Dere et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, the study by Castellan Baldan et al [79] provided evidence for disturbed sensorimotor gating in HDC knockout mice, as indicated by reduced pre-pulse inhibition (a neurophysiological phenomenon in which a weak pre-stimulus sound inhibits the reaction to a subsequent strong startling stimulus). Reduction in pre-pulse inhibition was also observed in patients with TS carrying the HDC W317X mutation [74], presumably as a result of elevation of striatal dopamine levels [82], which is in turn caused by a lack of inhibitory effect of histamine on dopamine release. This hypothesis was confirmed by the findings of the study by Castellan Baldan et al [79], who directly determined striatal dopamine using micro-dialysis: during the night-phase, when mice become active, striatal levels of histamine were found to be increased in wild-type mice, but not in HDC knockout mice; conversely, dopamine levels were significantly higher during the night phase in HDC knockout mice as compared to wild-type controls [79].…”
Section: The Hdc Knockout Mouse Modelmentioning
confidence: 99%
“…These mice are viable, fertile, and display no gross abnormalities except for abnormal mast cells (Ohtsu et al, 2001). However, there are permanent changes in the cortical-electroencephalogram and sleep-wake cycle: At moments when high vigilance is required, mice lacking brain histamine are unable to remain awake, a prerequisite condition for responding to behavioral and cognitive challenges (Parmentier et al, 2002), changes in learning ability (Dere et al, 2003), and increased obesity in high-fat diet-fed mice (Haas et al, 2008).…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%